Students' Perception Toward The Online English Learning Process During Covid-19 - Helmi Azizah; Ida Muliawati; Dara Yusnida (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2021)
Online English learning process, besides providing conveniences, there are also obstacles, this gives rise to various student perceptions. The Purposes of the research are to explore the student perception towards the online English learning process and to provide information about the factor influencing those perception during covid-19 at SMA N 7 Banda Aceh. The research design uses quantitative descriptive. The respondent of the research are students of SMA N 7 Banda Aceh from class X to class XII, while the sample of the research is taken from Class X IPAS 4 there are 21 respondent, class XI IPA 2 there are 27 respondent and class XII IPA 3 there are 20 respondents. Data collecting in this research is used a questionnaire. The data was automatically collected through data answers and recorded in the Google Form as a result of the data input. The majority of students had negative impressions about online English instruction, according to the findings of the study. Students do not understand the subject offered by the teacher, are less appealing, and have negative experience in online learning. Lack of strong signals to access content, a lot of consuming internet quota, less learning atmosphere, and the teacher presented is not maximally accepted by the students are some of the obstacles faced during online learning. For teachers, the approach to overcome online English learning challenges is to learn and share with other teachers, not just from one school, but from other schools as well, so that teaching techniques are more varied. Students are more engaged and enthusiastic to find out other learning references, and for school, there should be a new curriculum program to deal with the prolonged COVID-19 pandemic.